Defensive mixology: combining acquired chemicals towards defence. (22nd December 2014) - Mason, Peri A.; Singer, Michael S.
Summary: The myriad chemicals produced by plants may act in combination to enhance chemical defence against herbivores. Many animals have evolved the ability to harness plant secondary metabolites (PSMs) and other chemical resources for their own defence, but few studies have addressed the compelling notion that non‐human animals combine exogenous chemicals from different sources to defend themselves against predators, parasites and pathogens. We consider the use of ' defensive cocktails' from an evolutionary ecology perspective, introducing the term, 'acquired combinatorial chemical defence' (ACCD). We define ACCD as the adaptive use of multiple chemicals of discrete origin resulting in defence against natural enemies. First, we discuss the defining characteristics of ACCD: the ability to harness interspecific chemical variation, to independently regulate it, and to obtain defensive benefits via synergy that exceed those associated with single sources. Then, we describe three non‐mutually exclusive modes by which acquired chemicals may operate against natural enemies: different chemical resources may provide defence during different stages of development, may be effective against different enemies or may work additively or synergistically against a given enemy at a given developmental stage. Next, we describe possible avenues by which chemical combinations may be acquired by herbivores and other taxa, including the mixing of exogenous chemicals from different items in the diet and mixing chemicals of dietary origin with those from non‐food resources. We discuss possible costs of ACCD, including detoxification costs and interactions with the immune system, and discuss methods of testing for ACCD and its costs. Finally, we discuss the evolutionary prediction that herbivores may converge on the use of complementary combinations of chemical resources from the environment or chemical defence syndromes. Opportunities to combine chemical resources abound, suggesting that animal and human medication may be more closely aligned than previously recognized. Abstract : Lay Summary